PENGUATAN PERENCANAAN KEUANGAN DI RUMAH HIJRAH PONTIANAK - Hudaya , Afaqa; Zulfahmi; Saputro, Dio Bimo; Lestari, Dwi Ayu; Priastiwi, Dian (Gandhi: Jurnal Pengabdian Kepada Masyarakat, 2024)
Upgrading financial literacy in Rumah Hijrah Pontianak aims to empower the Rumah Hijrah Pontianak community by enhancing their financial literacy and investment knowledge. Through a series of workshops, seminars, and interactive discussions, the program will equip participants with practical skills for personal and group financial management. By fostering a deeper understanding of smart financial planning and investment strategies, this initiative seeks to encourage long-term financial growth and stability within the community. Ultimately, the goal is to increase community interest in financial planning, which will contribute to the sustainability of social and economic activities at Rumah Hijrah Pontianak.